Teachers’ and Students’ Perceptions of Ice Breaking and ItsContribution to Learning Motivation - M. Manugeren; Jumino Suhadi; Purwarno; Syafaruddin Marpaung (Jurnal Ragam Pengabdian, 2026)
Ice breaking is one of the pedagogical strategies used to create a conducive learning atmosphere and maintain student motivation. This study aims to analyze teachers' and students' perceptions of the use of ice breaking in learning and its contribution to learning motivation. The study used a qualitative descriptive approach conducted at SMA Negeri 2 Kota Tanjungbalai, involving 48 teachers and 36 students. Data were collected through classroom observation, open and semi-open questionnaires, interviews, and supporting documentation, then analyzed using thematic descriptive analysis techniques. The results showed that students had a positive perception of ice breaking because it created a more relaxed learning atmosphere, increased focus, and generated enthusiasm for learning. Teachers viewed ice breaking as a classroom management strategy that helped maintain student readiness and engagement, although its implementation still varied. This study concluded that ice breaking contributed positively to learning motivation when planned proportionally and adapted to classroom conditions